2022
DOI: 10.3389/fpls.2022.898969
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Inoculation Enhances Nutrient Absorption and Induces Insect-Resistant Defense of Elymus nutans

Abstract: The majority of terrestrial plants can form symbiotic associations on their roots with arbuscular mycorrhizal fungi (AMF) in the soil to stimulate the growth and nutrient uptake of the host plant and to improve plant resistance to insects and disease. However, the use of AMF for insect control on gramineous forages requires further study. Here, we evaluated the effects of AMF (Funneliformis mosseae) inoculation on the defense against Locusta migratoria attack in Elymus nutans. Inoculation assays showed that my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…berolinensis seedlings compared with nonmycorrhizal seedlings, resulting in a high JA content in plant tissues. The increase in the JA content induces chemical defense in plants, regulates the expression of plant secondary metabolite genes, and promotes the synthesis and accumulation of secondary metabolites, thus reducing herbivore preference, performance and abundance ( Zhang et al., 2022 ). We found that the content of total phenols and flavonoids in A. adenophora was significantly increased after inoculation with AMF ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…berolinensis seedlings compared with nonmycorrhizal seedlings, resulting in a high JA content in plant tissues. The increase in the JA content induces chemical defense in plants, regulates the expression of plant secondary metabolite genes, and promotes the synthesis and accumulation of secondary metabolites, thus reducing herbivore preference, performance and abundance ( Zhang et al., 2022 ). We found that the content of total phenols and flavonoids in A. adenophora was significantly increased after inoculation with AMF ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF), generally forming a symbiotic relationship with approximately 80% of terrestrial plants, can play a crucial role in the plants to face many biotic and abiotic stresses, such as pests, plant pathogens, drought, waterlogging, low temperature, and salinity ( Begum et al., 2019 ; Devi et al., 2022 ; Sivaprakasam Padmanaban et al., 2022 ; Zhang et al., 2022 ). Previous studies demonstrated the function of AMF in controlling anthracnose disease in many herbaceous plants such as Fragaria×ananassa Duch.…”
Section: Introductionmentioning
confidence: 99%
“…D-Limonene, p-xylene, and 1,3-diethylbenzene increase in Elymus nutans plants colonized with AMF ( Zhang et al., 2022 ). Under insect attack, 1,3-diethylbenzene and D-limonene can be generated to strengthen plant defenses and repel insects ( Agut et al., 2015 ; Kigathi et al., 2019 ; Mitra et al., 2021 ).…”
Section: Volatile Organic Compounds In Mycorrhizal Symbiosismentioning
confidence: 99%